WOMAN’S EXISTENCE IN THE NOVEL “KHUBZUN ‘ALAA TAWILATI AL-KHAL MILAD” BASED ON AN EXISTENTIALIST FEMINIST PERSPECTIVE - Imroatus Shalihah; Abdul Basid (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
One country that experiences gender inequality is Libya. Libyan had made women objects in decision-making, marginalized, and subordinated. This study aims to investigate the forms, factors, and impacts of women’s existence in the novel Khubzun ‘alaa Thawilati al-Khaal Milad by Muhammad al-Naas based on Simone de Beauvoir’s theory. This type of research is descriptive qualitative research. In analyzing the data, researchers read and understand the text in the novel and then record the data. The results of this study: are (1) the forms of women existence, namely ideal women, rejecting their femininity, free women, independent women, mystical women, and women images; (2) the factors of women existence, namely demands of having children, stereotypes, violence, domination, marginalization, objectification of decisions, community stigma and standardization of beauty; (3) the impacts of women existence: a) the impact of women existence on individuals is self-care, self-disappointment, resistance, smart women, not taking care of herself, being recognized, and attention, b) the impact of women existence in the family is not being appreciated by others, masculinity, family demands, and betrayal, c) the impact of women existence on society is not being appreciated by others, stereotypes, and exploitation.